Towards mixed fuels: the electrochemistry of hydrazine in the presence of methanol and formic acid. - Aldous, L; Compton, R (2011)
The electrochemistry of formic acid, carbon monoxide and methanol have been investigated and evaluated in combination with hydrazine. Hydrazine was observed to display the anticipated steady-state oxidation waves at platinum (Pt) microelectrodes by cyclic voltammetry, and upon introduction of carbon monoxide (CO) gas, the Pt surface was fully passivated (prior to CO oxidation). However, the two individual responses of hydrazine and formic acid (HCOOH) are to be additive when combined in solution. No detrimental effects were observed upon the hydrazine voltammetry, even in the presence of excess formic acid, despite formic acid clearly displaying characteristic self-poisoning tendencies (primarily due to the formation of CO) in its own voltammetry. Effects intermediate to those of CO and formic acid were observed when methanol was present. Currents were essentially additive at low methanol content, but hydrazine oxidation current decreased by about 40% when an 100-fold excess of methanol was present, corresponding to poisoning by methanol dehydrogenation intermediates. These results are discussed with relevance to mixed fuels for more flexible or powerful fuel cells, and the possible formation of a random microelectrode array (templated by strongly adsorbed poison) on the microelectrode surface.